UMP students helped victims of earthquake in Lombok - Muhammad Asyraf, Hasan; Mohd Ferdaus, Musa (2019)
Touched by the plight affected by victims of the earthquake in Lombok, whose homes were damaged and whose lost their loved ones in the disaster that happened on July 29, 2018, and again on August 6 and 19, 2018, a group of 10 Universiti Malaysia Pahang (UMP) students organised a humanity mission and were in the country from December 7 until 11, 2018.